2015
DOI: 10.1007/s00066-015-0875-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk profile for osteoradionecrosis of the mandible in the IMRT era

Abstract: BackgroundThe risk for osteoradionecrosis (ORN) of the mandible is positively related to bone volume exposed to > ~ 60 Gy. We hypothesized that in combined treatment, surgery may also be a risk factor.Patients and methodsThe impact of mandibular surgery on ORN in locally disease-free IMRT cohorts was retrospectively analyzed.ResultsBetween October 2002 and October 2013, 531 of 715 patients with oral cavity cancer (OCC), mesopharyngeal cancer (MC), or salivary gland tumor were treated with the mandible bone exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 14 publications
(15 reference statements)
1
49
2
1
Order By: Relevance
“…In a similar study from our institution, only 2 out of 168 patients developed ORN, with a median follow-up of 37.4 months [14]. However, recent studies with larger patient sample have reported higher prevalence of ORN; 21/334 (6.3%) and 36/531 (6.8%) patients developing ORN in patients treated with IMRT at a median follow-up of 31 months in patients treated for T1/T2 and mean follow-up of 38 months, respectively [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…In a similar study from our institution, only 2 out of 168 patients developed ORN, with a median follow-up of 37.4 months [14]. However, recent studies with larger patient sample have reported higher prevalence of ORN; 21/334 (6.3%) and 36/531 (6.8%) patients developing ORN in patients treated with IMRT at a median follow-up of 31 months in patients treated for T1/T2 and mean follow-up of 38 months, respectively [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with other recent reports exploring IMRT for oral cavity cancers, or the incidence of ORN in patients treated with IMRT for head and neck cancers. [19, 20] Studer et al recently reported 17% incidence of ORN in patients with oral cavity cancers treated with postoperative IMRT who received >60 Gy to the mandible. [19] A recent SEER medicare analysis of jaw complications in patients treated for oral cancers showed that patients treated with non-IMRT had 17% even rate compared to 14% in patients treated with IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoradionecrosis (ORN) remains a potentially serious complication following radiotherapy, even in the era of IMRT 8, 10, 22 . ORN is defined as an area of exposed bone greater than 1 cm in size in an area previously irradiated that failed to heal over a period of 3–6 months, and may require resection of the necrotic segment(s) of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…Reported incidence of ORN ranges from 6.3–6.8% of patients with oral and oropharyngeal cancer treated with IMRT. 8, 10 . High radiation dose and jaw trauma due to dental extraction remain major risk factors for this complication 10, 2326 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation